Esophageal ulcers caused by reactivation of ganglionary tuberculosis: a case report - Hadlich,Everton (2007)
The involvement of the esophagus in tuberculosis (TB) is extremely rare. This is a case report of an immunocompetent male patient, who presented ganglionary TB reactivation, with the development of extensive esophageal ulcers. The endoscopic approach made the diagnosis possible and there was a total resolution of the symptoms after the treatment.